Treatment with spermidine alleviates the effects of concomitantly applied cold stress by modulating Ca2+, pH and ROS homeostasis, actin filament organization and cell wall deposition in pollen tubes of Camellia sinensis - ÇETİNBAŞ GENÇ, ASLIHAN (ELSEVIER FRANCE-EDITIONS SCIENTIFIQUES MEDICALES ELSEVIER, 2020)
The aim of the current study was to examine the effect of spermidine treatment concomitant with cold stress on the elongation of Camellia sinensis pollen tube. When exogenous spermidine (0.05 mM) was applied concomitantly with cold stress, pollen germination rate and pollen tube length were significantly increased in comparison with cold stressed pollen tubes. In addition, spermidine treatment concomitantly with cold stress reduced pollen tube abnormalities induced by cold stress. Besides, cold-induced disorganizations of actin filaments were ameliorated after spermidine treatment along with cold stress because anisotropy levels of actin filaments in shank and apex of pollen tubes decreased. Changes in cold-induced callose distribution in the pollen tube cell wall were partially recovered after spermidine/cold stress treatment. Other cold-induced effects (decrease in Ca2+ content, reduction of pH gradient, accumulation of ROS) were reverted to adequate levels after spermidine treatment in conjunction with cold stress, indicating that pollen tubes are able to cope with stress. Thus, spermidine treatment reorganized the growth pattern of pollen tubes by modulating Ca2+ and ROS homeostasis, actin cytoskeleton organization, and cell wall deposition in Camellia sinensis pollen tubes under cold stress.
Keywords: Actin cytoskeleton; Cell wall; Cold stress; Pollen tube; Polyamines; Spermidine; MEMBRANE-ASSOCIATED CALCIUM; SUCROSE SYNTHASE; CELLULOSE SYNTHASE; CALLOSE SYNTHASE; LATRUNCULIN-B; NADPH OXIDASE; GROWTH; GERMINATION; TEMPERATURE; POLYAMINES